Analysis of Machinability of Inconel 718 in High Speed End Milling with Ceramic Inserts Under Room Temperature Conditions - Nurul Amin, A. K. M; Mokhtar, Suhaily; D. Arif, Muammer (Trans Tech Publications, Switzerland, 2012)
Abstract. Inconel 718 is used for high-temperature applications in aerospace, nuclear, and automotive industries due to its resistance, at high temperatures, to corrosion, fatigue, creep, oxidation, and deformation. Unfortunately, these same qualities also impair its machinability and researchers have investigated on ways to machine it economically. Some unconventional machining practices such as: Plasma Enhanced and Laser Assisted Machining etc. have been applied. However these practices increase the machining cost. This research investigated the viability of high speed end milling of Inconel 718 using circular Silicon Nitride (ceramic) inserts under room temperature conditions. Tool wear (flank and notch wear), machining vibration amplitude and average surface roughness were evaluated for the feasibility analysis. A vertical CNC mill was used to machine Inconel 718 samples using different combinations of three primary machining parameters: cutting speed, feed, and depth of cut. Vibration data acquisition device and Datalog DasyLab 5.6 software were used to analyze machining vibration. Scanning Electron Microscope (SEM) and surface profilometer were utilized to measure tool (flank and notch) wear and surface roughness, respectively. It was observed that the machining vibrations, in high speed machining, was reasonable (0.045 V on the average). This resulted in acceptable tool wear (averages: flank wear = 0.25 mm, notch wear = 0.45 mm) and semi-finished surface roughness (0.30 μm) measured after every 30 mm length of cut. Thus, room temperature high speed machining of Inconel 718 using circular silicon nitride inserts is a practical option.